Respuesta :
x = 8(y-1)^2 - 15
Standard form looks like this, x^2 -6x + 8, or y^2 - 6y + 8
To convert your equation into standard form all we have to do is expand it fully:
x = 8(y-1)^2 - 15
x = 8(y-1)(y-1) - 15
x = 8(y^2 -2y + 1) - 15
x = 8y^2 -16y + 8 - 15
x = 8y^2 -16y - 7
Standard form looks like this, x^2 -6x + 8, or y^2 - 6y + 8
To convert your equation into standard form all we have to do is expand it fully:
x = 8(y-1)^2 - 15
x = 8(y-1)(y-1) - 15
x = 8(y^2 -2y + 1) - 15
x = 8y^2 -16y + 8 - 15
x = 8y^2 -16y - 7
Answer:
The standard form of the equation is:
[tex]x=8y^2-16y-7[/tex]
Step-by-step explanation:
We know that the standard form of a quadratic equation is given by the expression:
[tex]x=ay^2+by+c[/tex]
where a,b and c are real numbers.
and a≠0
Here we are given the vertex form of the equation of a parabola by:
[tex]x=8(y-1)^2-15[/tex]
Now, on expanding the parentheses term by using the formula:
[tex](a-b)^2=a^2+b^2-2ab[/tex]
Here a=y and b= 1
Hence, we have:
[tex]x=8(y^2+1-2y)-15\\\\i.e.\\\\x=8\times y^2+8\times 1-2y\times 8-15\\\\i.e.\\\\x=8y^2+8-16y-15\\\\i.e.\\\\x=8y^2-16y+8-15[/tex]
( Since, in the last step we combined the constant term i.e. 8 and -15 )
Hence, we get the standard form of the equation as:
[tex]x=8y^2-16y-7[/tex]